2016
DOI: 10.1186/s12872-016-0373-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the longitudinal changes in infarct heterogeneity post myocardial infarction

Abstract: BackgroundInfarct heterogeneity, as assessed by determination of the peri-infarct zone (PIZ) by cardiac magnetic resonance imaging, has been shown to be an independent predictor for the development of cardiac arrhythmias and mortality post myocardial infarction (MI). The temporal evolution of the PIZ post MI is currently unknown. Thus, the main objective of our study was to describe the temporal evolution of the PIZ over a 6 month time period in contemporarily managed ST elevation myocardial infarction (STEMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…Similarly, the maximum intensity region of the myocardium was chosen as the infarct and the peak signal intensity among all pixels in the infarct regions ( Peakinfarct) was determined. The signal intensity (SI) thresholds for determining the infarct core and peri‐infarct gray zone using FWHM were as follows: SIcore>0.5*Peakinfarct and Peakremote<SIgrayzone<0.5*Peakinfarct, where SIcore is the signal intensity of a pixel classified as the infarct core and SIgrayzone is the signal intensity of a pixel classified as the peri‐infarct gray zone 7,31 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the maximum intensity region of the myocardium was chosen as the infarct and the peak signal intensity among all pixels in the infarct regions ( Peakinfarct) was determined. The signal intensity (SI) thresholds for determining the infarct core and peri‐infarct gray zone using FWHM were as follows: SIcore>0.5*Peakinfarct and Peakremote<SIgrayzone<0.5*Peakinfarct, where SIcore is the signal intensity of a pixel classified as the infarct core and SIgrayzone is the signal intensity of a pixel classified as the peri‐infarct gray zone 7,31 …”
Section: Methodsmentioning
confidence: 99%
“…The signal intensity (SI) thresholds for determining the infarct core and peri-infarct gray zone using FWHM were as follows: SI core > 0.5 * Peak infarct and Peak remote < SI grayzone < 0.5 * Peak infarct , where SI core is the signal intensity of a pixel classified as the infarct core and SI grayzone is the signal intensity of a pixel classified as the peri-infarct gray zone. 7,31 In the multi-contrast volumetric images, signal characteristics over multiple TIs for a single voxel can be represented by two tissue-dependent MR parameters including the apparent T 1 relaxation (T * 1 ) and steady-state magnetization (M ss ). 28 In this study, the two MR parameters were calculated by fitting voxel-wise signal intensities at six inversion times into a parametric exponential recovery model.…”
Section: Infarct Heterogeneity Analysismentioning
confidence: 99%
“…Recent studies have revealed PIR represents the nexus for active remodeling characterized by extracellular matrix formation, angiogenesis, oxidative stress, mitochondrial energetics, apoptosis and inflammation [9,[30][31][32]. Those active and dynamic reactions could lead to its heterogeneity and arrhythmogenic substrates.…”
Section: Pir Characterization By Memrimentioning
confidence: 99%
“…56 Twenty-one patients with reperfused STEMI underwent CMR-LGE at 2 days, 3 weeks and 6 months post-MI. Core infarct sizes declined significantly over time in both patients with and without microvascular obstruction (no-reflow).…”
Section: Cmr Assessment Of Myocardial Scar and Scar Heterogeneitymentioning
confidence: 99%